2013
DOI: 10.1177/1060028013510898
|View full text |Cite
|
Sign up to set email alerts
|

Medication Regimen Complexity and Hospital Readmission for an Adverse Drug Event

Abstract: Complex medication regimens at hospital admission are predictive of rehospitalizations for ADEs. This finding suggests that medication regimen complexity be considered as a target for interventions to decrease the risk for readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 26 publications
4
84
0
3
Order By: Relevance
“…Previous studies that seeked to exploit EHR information with a similar postulate have mainly been developing score-based techniques. For instance the works found in [33,34,35,5] also assume that the complexity of the patient's medication regimen is a good indicator of the complexity of the patient's condition. The existence of correlations between MRCI at admission and occurence of complications is empirically demonstrated in the work of Lepelley et al [5].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies that seeked to exploit EHR information with a similar postulate have mainly been developing score-based techniques. For instance the works found in [33,34,35,5] also assume that the complexity of the patient's medication regimen is a good indicator of the complexity of the patient's condition. The existence of correlations between MRCI at admission and occurence of complications is empirically demonstrated in the work of Lepelley et al [5].…”
Section: Related Workmentioning
confidence: 99%
“…need to take medications with food) also contribute to complexity. Medication regimen complexity has been associated with poor medication adherence [2,3], hospital readmission [4][5][6], adverse drug events [5], poor quality of life [7] and hospital discharge directly to an aged care facility [8]. However, it is unclear to what extent regimen complexity may confer a greater risk of adverse events over and above that associated with number of medications.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have suggested medication parameters such as use of high-risk medication and polypharmacy (use of five or more medications) that may increase the risk of rehospitalization. 17) Given that elderly patients often take multiple medications and are more susceptible to adverse drug events, it is particularly important to ensure that a complete and accurate list of medications is obtained at discharge. 18,19) Age-related pharmacodynamic and pharmacokinetic changes increase the susceptibility of elderly patients to adverse reactions from medications.…”
Section: Discussionmentioning
confidence: 99%